Mental Health, Emotional Regulation, and Psychosocial Work Factors Among Scientific Researchers: A Cross-Sectional Study from Paraguay - Julio Torales; Anthon Torres-Romero; Iván Barrios; Marcelo O’Higgins; Tomás Caycho-Rodríguez; João Mauricio Castaldelli-Maia; Antonio Ventriglio (Brain Sciences)
Background: This study examined the prevalence of mental health issues among Paraguayan researchers and their relationships with emotional regulation and psychosocial factors. Methods: A cross-sectional survey of 235 researchers was conducted using validated instruments: the Depression, Anxiety, and Stress Scale (DASS-21); the Job Content Questionnaire (JCQ); and the Difficulties in Emotion Regulation Scale (DERS). Sociodemographic, academic, and behavioral variables were also analyzed. Results: Findings revealed significant rates of depression (26.4%), anxiety (30.6%), and stress (32.3%), with female researchers reporting nearly twice the rates of anxiety and stress compared to males. Researchers with doctoral degrees exhibited lower anxiety levels, emphasizing the protective role of advanced academic qualifications. Conversely, younger and early-career researchers were more vulnerable to psychological distress. High job demands and emotional dysregulation were strongly associated with poorer mental health outcomes, while hazardous alcohol consumption and low physical activity further exacerbated risks. Conclusions: These findings highlight the urgent need for institutional reforms to prioritize mental health and well-being in academic environments. By advancing the understanding of occupational health in resource-limited settings, this study provides actionable recommendations to improve the working conditions and mental health of researchers in Paraguay and beyond.